A method for surface modification of implants for diabetic bone repair
Patent Information
- Application Number
- CN202511313277.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2045-09-15
AI Technical Summary
因此,仅仅通过抵御氧化应激往往不能有效促进糖尿病微环境植入体-骨整合,需充分考虑重塑免疫稳态
与现有技术相比较,本发明的有益效果在于:现有技术中,锰基纳米酶(如MnO2、Mn3O4)虽具有良好的ROS清除能力,但单一抗氧化策略难以逆转糖尿病微环境中的免疫紊乱。本发明通过将Mn3O4-BSA纳米酶与中药免疫调节剂18β-甘草次酸(GA)偶联物(CS-GA)结合,构建了兼具抗氧化和免疫调节功能的生物活性界面(LBL-GA@Mn),实现了“抗氧化-免疫调控-抗炎-促修复”的协同作用,突破了单一疗法在糖尿病骨缺损治疗中的局限性。具体效果分析如下:
Smart Images

Figure CN121102581B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical biological implant materials, specifically relating to a method for modifying the surface of an implant for bone repair in diabetes, which is suitable for the field of bone injury repair implant materials. Background Technology
[0002] Generally, diabetic patients experience a decreased bone turnover rate, and changes in the properties and microstructure of bone material, increasing the risk of fractures and becoming a new and serious complication of diabetes. Clinically, bone trauma (bone defects, fractures, etc.) combined with diabetes increases surgical risks, treatment difficulty, and prolongs healing time, troubling countless doctors and patients, which has increased attention to the treatment of diabetic bone trauma.
[0003] Treatment of bone trauma typically requires implants for repositioning and internal fixation. Common implants include stainless steel, titanium and titanium alloys, and PEEK. In recent years, advancements in surface modification technology, such as adding bioactive factors, nanomaterials, or altering surface roughness, have endowed implants with excellent bioactivity, resulting in good early bone integration and high surgical success rates in healthy individuals. However, diabetes is considered a relative contraindication for implant surgery and has long been a pressing clinical challenge. Studies have shown that diabetic patients have a 50% higher risk of peri-implantitis and a 20% higher implant failure rate. This is because diabetic patients have impaired bone metabolism, resulting in a pathological microenvironment characterized by persistent chronic inflammation, which hinders implant-bone integration. Therefore, developing implant materials suitable for diabetic bone trauma and improving internal fixation success rates is of significant practical importance for promoting the development of the implantable medical device industry.
[0004] In recent years, as researchers have gained a deeper understanding of the pathological microenvironment of diabetes, they have discovered that in addition to the accumulation of advanced glycation end products (AGEs) and persistent chronic inflammation, the bone defect microenvironment in diabetes is also accompanied by excessive oxidative stress and an imbalanced immune homeostasis. Studies have shown that AGEs accumulated at the site of diabetic bone defects lead to mitochondrial dysfunction in surrounding cells, abnormal energy metabolism activates the production of reactive oxygen species (ROS) and inhibits the expression of antioxidant enzymes (SOD, CAT, and GSH-Px). ROS that cannot be broken down in time further cause mitochondrial fragmentation and more severe dysfunction, leading to oxidative stress. On the one hand, oxidative stress not only directly inhibits the migration, proliferation, and differentiation potential of bone marrow mesenchymal stem cells (BMSCs), but also significantly hinders angiogenesis and bone repair processes by affecting vascular endothelial cell function and causing microvascular complications. On the other hand, oxidative stress can also lead to immune dysregulation, causing macrophages to be continuously activated into the pro-inflammatory M1 type, hindering their conversion into the anti-inflammatory M2 type. This results in the overexpression of pro-inflammatory cytokines (TNF-α, IL-1β, etc.), exacerbating the inflammatory response and further interfering with the bone repair process. Furthermore, the vicious cycle of "oxidative stress-immune dysregulation-chronic inflammation" leads to impaired or stalled healing of diabetic bone defects and causes damage to surrounding bone. Therefore, designing implant surface interfaces with local antioxidant and immunomodulatory capabilities has potential application value in improving implant-bone integration and increasing the success rate of internal fixation in diabetic conditions.
[0005] In recent years, manganese-based antioxidant nanozymes (MnO2, Mn3O4) have shown promising applications in anti-inflammatory and anti-oxidative stress therapy due to their low production cost, broad-spectrum ROS scavenging activity, good stability, and biocompatibility. For example, hydrogels doped with MnO2 nanozymes significantly accelerate wound healing under abnormal inflammatory conditions by scavenging excess ROS and generating oxygen (O2) at diabetic wound sites. Chondroitin sulfate hydrogels doped with Mn3O4 treat osteoarthritis by scavenging excess ROS in the osteoarthritis microenvironment and protecting chondrocytes from oxidative damage caused by uncontrolled inflammatory responses. However, under diabetic conditions, oxidative stress causes immune homeostasis imbalance, leading to prolonged M1 (pro-inflammatory) macrophage retention and hindering their conversion to M2 (anti-inflammatory) macrophages. M1 (pro-inflammatory) macrophages continuously secrete pro-inflammatory factors and extend the inflammatory response to surrounding bone tissue, severely hindering implant-bone integration. Therefore, simply resisting oxidative stress is often insufficient to effectively promote implant-bone integration in the diabetic microenvironment; remodeling immune homeostasis must be fully considered.
[0006] Numerous studies have shown that the "drug-device combination" approach, combining traditional Chinese medicine immunomodulators with biomaterials to exert immunomodulatory effects, can significantly accelerate the damage repair process and has promising clinical application prospects. 18β-Glycyrrhetinic acid (GA) is an active ingredient with a pentacyclic triterpenoid structure extracted from licorice. It possesses immunomodulatory effects and has no significant side effects. Summary of the Invention
[0007] Addressing the current clinical challenges of poor bone integration and low internal fixation success rates in implants within the diabetic pathological microenvironment, this invention combines the advantages of novel materials (antioxidant nanozymes) and traditional Chinese medicine (TCM immunomodulators). Utilizing layer-by-layer self-assembly (LBL) technology, this invention constructs a bioactive interface (LBL-GA@Mn) containing antioxidant nanozymes and TCM immunomodulators on the implant surface. The specific technical solution is as follows: The present invention provides a surface-modified bone injury repair implant, wherein the surface of the implant is modified with manganese-based antioxidant nanozyme and 18β-glycyrrhetinic acid conjugate.
[0008] Preferably, the manganese-based antioxidant nanoenzyme is a Mn3O4-BSA antioxidant nanoenzyme.
[0009] Preferably, the 18β-glycyrrhetinic acid conjugate is chitosan-18β-glycyrrhetinic acid conjugate (CS-GA).
[0010] Preferably, the implant is a metal implant material including titanium, titanium alloy, stainless steel or cobalt-based alloy.
[0011] This invention also provides a method for preparing the surface-modified bone injury repair implant, comprising the following steps: Step 1: Prepare Mn3O4-BSA antioxidant nanozymes by hydrothermal method and ultrasonic treatment; Step 2: Prepare chitosan-18β-glycyrrhetinic acid conjugate (CS-GA) by grafting 18β-glycyrrhetinic acid onto chitosan via EDC / NHS acylation reaction. Step 3: Using layer-by-layer self-assembly (LBL) technology, a gelatin (Gel) / CS-GA polyelectrolyte multilayer membrane structure was constructed on the implant surface, and Mn3O4-BSA was used as the intercalation component of the multilayer membrane to prepare a bioactive surface LBL-GA@Mn modified implant.
[0012] Preferably, step one includes: dissolving manganese acetate in ethanol, sealing the solution and heating it to react, cooling it after the reaction is complete, and centrifuging to separate the nanoparticles; adding Mn3O4 solution to BSA solution, sonicating the reaction, and centrifuging to collect the nanoparticles after the reaction is complete, and the resulting product is Mn3O4-BSA nanoparticles.
[0013] Preferably, step two includes: preparing chitosan solution and 18β-glycyrrhetinic acid (GA) solution separately for later use; adding EDC and NHS to the GA solution to activate GA; adding the activated GA solution to the chitosan solution for reaction; and obtaining chitosan-18β-glycyrrhetinic acid conjugate CS-GA after post-treatment.
[0014] Preferably, step three includes: first, preparing CS-GA solution, Gel solution, PEI solution and BSA-Mn3O4 solution for later use; then, immersing the clean implant to be modified in polyethyleneimine (PEI) solution to obtain a PEI-functionalized interface; then, immersing the PEI-pretreated implant in Gel solution, CS-GA solution and Mn3O4-BSA antioxidant nanozyme solution in sequence, repeating the previous immersion step, and finally obtaining an implant with an LBL-GA@Mn bioactive interface.
[0015] Preferably, in step three, polyethyleneimine (PEI) is used as the initiating layer, CS-GA as the cationic polyelectrolyte, gelatin (Gel) as the anionic polyelectrolyte, and Mn3O4-BSA antioxidant nanozyme as the intercalation component.
[0016] The present invention also provides the application of the surface-modified bone injury repair implant, that is, the preparation of the implant for treating bone injury sites in diabetic patients.
[0017] Beneficial effects Compared with existing technologies, the beneficial effects of this invention are as follows: While existing manganese-based nanozymes (such as MnO2 and Mn3O4) possess good ROS scavenging capabilities, single antioxidant strategies are insufficient to reverse immune dysregulation in the diabetic microenvironment. This invention, by combining Mn3O4-BSA nanozymes with the traditional Chinese medicine immunomodulator 18β-glycyrrhetinic acid (GA) conjugate (CS-GA), constructs a bioactive interface (LBL-GA@Mn) possessing both antioxidant and immunomodulatory functions. This achieves a synergistic effect of "antioxidant-immunomodulation-anti-inflammatory-promoting repair," overcoming the limitations of single-therapy approaches in the treatment of diabetic bone defects. Specific effects are analyzed below: (1) The CS-GA / Gel polyelectrolyte multilayer membrane structure constructed in this invention can effectively achieve high-efficiency loading of traditional Chinese medicine immunomodulator (18β-glycyrrhetinic acid), which can easily achieve in situ cell uptake and subsequent cell function regulation, effectively solving the problems of low bioavailability and potential side effects. (2) The LBL-GA@Mn bioactive interface, which combines antioxidant stress and immune regulation properties, can restore / regulate cellular physiological functions through "spatiotemporal coupling" and is the key to effectively improving the pathological microenvironment of diabetic bone injury: On the one hand, it exerts antioxidant stress under the action of Mn3O4-BSA antioxidant nanozyme, effectively removes excess H2O2 in the microenvironment and reduces its toxic effects on cells; on the other hand, it further exerts immune regulation under the action of CS-GA, effectively increasing the proportion of anti-inflammatory M2 macrophages around the implant and significantly improving the inflammatory microenvironment. (3) This invention is a new attempt to organically integrate new materials (antioxidant nanoenzymes) with traditional Chinese medicine (Chinese medicine immunomodulators), which is expected to break through the limitations of single therapy and provide new strategies and ideas for synergistic treatment of inflammatory bone diseases such as diabetic bone defects. Attached Figure Description
[0018] Figure 1 Transmission electron microscopy (TEM) images of Mn3O4 and Mn3O4-BSA nanoparticles from Example 1.
[0019] Figure 2 In Figure a, the surface zeta potential changes during the construction of Mn3O4-BSA nanoparticles in Example 1 are shown. Figure 2 In the image, b is the XPS spectrum of Mn3O4-BSA.
[0020] Figure 3 The effects of different concentrations of Mn3O4-BSA on H2O2, ·OH, and O2· in Example 1. - Free radical scavenging efficiency graph.
[0021] Figure 4 The Raman spectra of CS, GA and CS-GA in Example 1 are shown.
[0022] Figure 5 The images show the 1H NMR spectra of GA and CS-GA from Example 1.
[0023] Figure 6 These are representative fluorescence images of ROS levels in macrophages after different treatments in Example 2.
[0024] Figure 7 These are representative fluorescence images of mitochondrial membrane potential in macrophages after different treatments in Example 2.
[0025] Figure 8 This is a statistical graph showing the level of ATP production by macrophages at different interfaces in Example 2.
[0026] Figure 9 These are representative fluorescence images of the expression of M1 and M2 biomarkers in macrophages after different treatments in Example 2.
[0027] Figure 10 Example 2 further examined the ratio of M1 and M2 macrophages at different interfaces using flow cytometry.
[0028] Figure 11 This is a graph showing the corresponding levels of pro-inflammatory and anti-inflammatory factors secreted by macrophages at different interfaces in Example 2.
[0029] Figure 12 Immunofluorescence staining images of 8-OHdG expression in bone tissue surrounding different implants.
[0030] Figure 13 Immunofluorescence staining images of M1 and M2 macrophages surrounding different titanium-based implants.
[0031] Figure 14 Micro-CT images and quantitative analysis of different implants. Detailed Implementation
[0032] The present invention is described in detail through the following embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection of the present invention, and all compositions based on the core substances of the present invention as the main components are within the scope of protection of the present invention.
[0033] Example 1 This embodiment includes the following steps: Step 1: Preparation of Mn3O4-BSA antioxidant nanozymes Mn3O4-BSA antioxidant nanozymes were prepared by hydrothermal method and ultrasonic treatment: (1) 0.408 g of manganese acetate was dissolved in 20 mL of anhydrous ethanol and magnetically stirred for 30 min until it was completely dissolved and the solution turned pink; (2) The solution was then transferred to a special Teflon bottle and sealed in a stainless steel reactor. The reactor was then placed in a muffle furnace and reacted at 120 °C for 24 hours; (3) After the reaction was completed, the reactor was cooled to room temperature and the brown nanoparticles were collected by centrifugation (12000 rpm); (4) Mn3O4 solution (1 mg / mL) was prepared with ultrapure water and slowly added to BSA solution (1 mg / mL). The mixed solution was placed in an ice bath and ultrasonically reacted for 2 h with an ultrasonic parameter of 40 KHz; (5) After the reaction was completed, the nanoparticles were collected by centrifugation (12000 rpm). The product obtained was Mn3O4-BSA nanoparticles.
[0034] Step 2: Preparation of chitosan-18β-glycyrrhetinic acid conjugate (CS-GA) 18β-glycyrrhetinic acid was grafted onto chitosan via EDC / NHS acylation reaction: (1) 0.5 g of chitosan was weighed and a chitosan solution with a mass fraction (wt%) of 0.5% was prepared (100 mL, with acetic acid solution added dropwise to promote dissolution). The solution was magnetically stirred for 12 h to obtain a clear and transparent chitosan solution; (2) 60 mg of 18β-glycyrrhetinic acid was weighed and a 18β-glycyrrhetinic acid (GA) solution with a concentration of 4 mg / mL (15 mL) was prepared using N,N-dimethylformamide (DMF) as the solvent. The solution was magnetically stirred until dissolved; (3) 72 mg of EDC and NHS were weighed and added to the GA solution to activate the GA. The mass ratio of EDC / NHS to GA was controlled at 1.2:1, and the reaction was magnetically stirred for 4 h at room temperature; (4) The activated GA solution (15 mL) was added dropwise to the chitosan solution (24 mL). In mL), the pH of the reaction solution was kept at 5.0 and the reaction was magnetically stirred at room temperature for 72 h; (5) After the reaction was completed, the mixture was dialyzed with distilled water for 72 h to remove unreacted reagents, and then freeze-dried to obtain CS-GA.
[0035] Step 3: Preparation of LBL-GA@Mn bioactive interface A multilayer polyelectrolyte membrane structure is constructed on the surface of the implant using layer-by-layer self-assembly (LBL) technology. In this embodiment, a titanium implant is used as an example. Polyethyleneimine (PEI) is used as the initiating layer, CS-GA is used as the cationic polyelectrolyte, gelatin is used as the anionic polyelectrolyte, and Mn3O4-BSA antioxidant nanozyme is used as the intercalation component. (1) Prepare a CS-GA solution with a concentration of 2 mg / mL using acetic acid solution (0.1%, v / v), stir magnetically until the solution is clear, and then adjust the pH to about 6.5 with NaOH solution; (2) Prepare a Gel solution with a concentration of 2 mg / mL, a PEI solution with a concentration of 2 mg / mL, and a BSA-Mn3O4 solution with a concentration of 20 μg / mL using deionized water; (3) Immerse a clean titanium sheet (1.5 cm in diameter) in the PEI solution, let it stand for 30 min, and then take it out and gently rinse it with deionized water 3 times to obtain a PEI-functionalized interface; (4) Immerse the PEI-pretreated titanium sheet in the Gel solution, CS-GA solution, and Mn3O4-BSA antioxidant nanoenzyme solution in sequence, and take it out after standing for 10 min each time, and then gently rinse it with deionized water 3 times for 3 min each time; (5) Repeat step (4) 5 times to finally obtain the LBL-GA@Mn bioactive interface implant.
[0036] The product obtained by adopting the above implant surface modification strategy is a titanium-based implant bioactive interface suitable for the treatment of diabetic bone trauma. During the overall construction process, many factors affect the synthesis of Mn3O4-BSA antioxidant nanozyme, CS-GA polycationic electrolyte, and LBL-GA@Mn bioactive interface. These include the concentrations and reaction time of Mn3O4 and BSA during Mn3O4-BSA synthesis, the EDC / NHS to GA feed ratio during CS-GA synthesis, the concentration of Mn3O4-BSA during layer-by-layer self-assembly interface construction, and the number of LBL repetitions. Different control conditions will directly affect the construction of the bioactive interface.
[0037] This embodiment focuses on investigating the concentrations and reaction times of Mn3O4 and BSA during the synthesis of Mn3O4-BSA, the feed ratio of EDC / NHS to GA during the synthesis of CS-GA, the concentration of Mn3O4-BSA during the layer-by-layer self-assembly interface construction, and the number of repetitions of LBL.
[0038] The results showed that when 1 mg / mL Mn3O4 and 1 mg / mL BSA were reacted and the reaction was carried out in an ice bath with sonication for 2 h, a stable Mn3O4-BSA antioxidant nanozyme with good scavenging activity against a variety of free radicals could be obtained. When 4 mg / mL GA solution (15 mL, 60 mg) was activated with 72 mg EDC and NHS, and the mass ratio of EDC / NHS to GA was controlled at 1.2:1, CS-GA with good immunomodulatory activity could be obtained. When the concentration of CS-GA and gelatin (Gel) was selected as 2 mg / mL, and 20 μg / mL Mn3O4-BSA was selected as the intercalation component, the bioactive interface constructed by LBL repeated 5 times had low cytotoxicity, good antioxidant activation and immunomodulatory effects.
[0039] In this embodiment, as Figure 1 The transmission electron microscopy image shown indicates that the Mn3O4-BSA antioxidant nanozyme has a uniform morphology, exhibits good dispersibility, and has a size of approximately 8.41 nm. Figure 2 In Figure 'a', the surface zeta potential changes during the construction of Mn3O4-BSA nanoparticles. The results show that the zeta potentials of Mn3O4 and Mn3O4-BSA are -2.9 eV and -15.3 eV, respectively. Figure 2 Figure b shows the XPS spectrum of Mn3O4-BSA, indicating the presence of elements C, N, O, and Mn in Mn3O4-BSA. Furthermore, two characteristic peaks were observed at 643.21 eV and 641.50 eV, which are attributed to Mn 2p. 1 / 2 and Mn 2p3 / 2 peak. Figure 3 The effects of different concentrations of Mn3O4-BSA on H2O2, ·OH, and O2· - The free radical scavenging ability of Mn3O4-BSA was investigated, and the results showed that Mn3O4-BSA exhibited concentration-dependent scavenging activity against different free radicals. Figure 4 The Raman spectra of CS, GA, and CS-GA are shown. The results indicate that the Raman spectrum of GA is at 1667 cm⁻¹ due to the C=O stretching vibration of the carboxyl group in the GA molecule. -1 It shows typical characteristic peaks at 1667 cm⁻¹; however, in the Raman spectrum of CS-GA, 1667 cm⁻¹... -1 The absorption peak at 1645 cm⁻¹ disappears, and at the same time, the absorption peak at 164 -1 A new absorption peak appeared at the point, which is due to the C=O stretching vibration in the amide group, proving that GA is grafted onto CS. Figure 5 The images show the 1H NMR spectra of GA and CS-GA. In CS-GA, a distinct characteristic peak of active hydrogen in the amide was observed at a chemical shift of 6.20, indicating that CS and GA formed an amide bond through the reaction. Meanwhile, the characteristic peak of methyl groups in GA was also observed at chemical shifts of 1.0 to 1.5, proving that CS-GA was successfully synthesized.
[0040] Example 2 The LBL-GA@Mn bioactive interface implant constructed in Example 1 above was used to evaluate its antioxidant stress capacity, immunomodulatory capacity, and anti-inflammatory effect in vitro. In this example, normal macrophages (RAW264.7, 5×10⁻⁶ cells) were used. 4 cells / cm 2 Using LBL-GA@Mn as a model cell, macrophages were pretreated for 12 h with simulated diabetic microenvironment conditions (25.5 mM glucose + 100 ng / mL LPS). Activated macrophages were then co-incubated with different titanium-based interfaces to investigate the ROS scavenging ability of LBL-GA@Mn, its ability to promote M2 macrophage polarization, and the secretion levels of pro-inflammatory / anti-inflammatory cytokines. The experimental setup included a normal control group (Control), LPS + Ti, LPS + LBL, LPS + LBL-GA, LPS + Mn, and LPS + LBL-GA@Mn. Specific experiments included: Experiment 1: Evaluation of Endogenous ROS Levels After co-culturing for 24 h, 500 μL of the ROS fluorescent probe 2',7'-dichlorofluorescein diacetate (DCFH-DA, 10 μM) was added to each group. After incubation at 37 ℃ for 30 min, the cells were gently rinsed three times with PBS buffer, and the ROS level inside the cells was observed using an inverted fluorescence microscope.
[0041] Experiment 2: Evaluation of mitochondrial membrane potential After co-culturing for 24 h, 500 μL of JC-1 working solution was added to each group. After incubation at room temperature in the dark for 30 minutes, the cells were gently rinsed three times with JC-1 staining buffer. Changes in mitochondrial membrane potential inside the cells were observed using an inverted fluorescence microscope.
[0042] Experiment 3: Detection of Intracellular ATP Content After co-culturing for 24 h, 200 μL of cell lysis buffer was added to each group. The cells were ground multiple times to ensure complete lysis. The lysis buffer was transferred to a 1.5 mL centrifuge tube and centrifuged at 4 °C for 5 min. The supernatant was collected. A standard curve and ATP detection working solution were prepared according to the kit instructions. 100 μL of ATP detection working solution was added to each group. Then, 50 μL of sample was added to each well. After mixing, the intensity was measured using a chemiluminescence analyzer, and the ATP concentration was calculated based on the standard curve.
[0043] Experiment 4: Evaluation of M2 type polarization capacity of macrophages After co-culturing for 48 h, immunofluorescence staining was performed using primary antibodies against M1 macrophage markers (iNOS), M2 macrophage markers (CD206), and corresponding secondary fluorescent antibodies. The stained cells were then observed and analyzed using CLSM. In addition, macrophages at different interfaces were collected using a cell scraper and co-incubated with PE-labeled CD86 antibody and Cy5.5-labeled CD206 antibody. After centrifugation, excess unbound antibodies were washed away with 500 μL of PBS containing 1% BSA. After reselection, the macrophage phenotype was detected by flow cytometry.
[0044] Experiment 5: Detection of intracellular pro-inflammatory / anti-inflammatory cytokine levels After co-culturing for 48 h, culture medium from macrophages in different groups was collected, and the secretion levels of pro-inflammatory factors (TNF-α, IL-6) and anti-inflammatory factors (TGF-β, IL-10) were quantitatively detected using an ELISA kit.
[0045] In this embodiment: like Figure 6 The images show representative fluorescence images of ROS levels in macrophages after different treatments. Stronger green fluorescence indicates higher ROS levels. The results show that macrophages stimulated by LPS and high glucose exhibit significant green fluorescence, while the green fluorescence in macrophages significantly decreased after treatment with LBL-GA and LBL-Mn. In contrast, the LBL-GA@Mn treatment group showed the weakest green fluorescence, significantly reducing intracellular oxidative stress levels. Figure 7The images show representative fluorescence images of mitochondrial membrane potential in macrophages after different treatments. Under normal conditions, the mitochondrial membrane potential is high, and JC-1 forms polymers and emits red fluorescence. In contrast, when the mitochondrial membrane is damaged, JC-1 forms monomers and emits green fluorescence. The results indicate that the diabetic microenvironment simulated by LPS and high-glucose culture medium causes mitochondrial damage and a decrease in mitochondrial membrane potential. In the LBL-GA, LBL@Mn, and LBL-GA@Mn groups, a decrease in green fluorescence and an increase in red fluorescence were observed. The membrane potential of the LBL-GA@Mn group was close to that of the Control group, proving that the LBL-GA@Mn interface can restore the abnormal mitochondrial membrane potential to a normal level.
[0046] like Figure 8 The results show the ATP production levels of macrophages at different interfaces. Under normal conditions, when mitochondria are undamaged, cells produce sufficient ATP. However, under LPS and high glucose stimulation, macrophage mitochondrial function is abnormal and ATP synthesis is severely affected. In contrast, ATP production of macrophages at the LBL-GA@Mn interface is largely restored, fully demonstrating the ability of bioactive interfaces to mitigate oxidative stress damage.
[0047] like Figure 9 As shown, representative fluorescence images of M1 and M2 markers in macrophages after different treatments were obtained. The results showed that after LPS and high glucose induction, macrophages were stimulated to polarize to the M1 phenotype. After LBL-GA@Mn treatment, the expression of iNOS (M1 marker) was significantly reduced, while the expression of CD206 (M2 marker) was significantly increased. This indicates that LBL-GA@Mn can effectively inhibit the M1 (pro-inflammatory) polarization of macrophages and induce them to transform into the M2 (anti-inflammatory) phenotype.
[0048] like Figure 10 As shown, the proportions of M1 and M2 macrophages at different interfaces were further detected by flow cytometry. The results showed that, compared with the Ti group, the proportion of M1 macrophages in the LBL-GA, LBL@Mn, and LBL-GA@Mn groups decreased significantly, while the proportion of M2 macrophages increased significantly. Among them, the M2 / M1 ratio in the LBL-GA@Mn group was significantly higher than that in the LBL-GA and LBL@Mn groups, indicating that the LBL-GA@Mn interface can effectively promote the M2 transformation of macrophages.
[0049] like Figure 11As shown, the levels of pro-inflammatory and anti-inflammatory factors secreted by macrophages at different interfaces were compared. The results indicated that after LPS and high glucose induction, macrophages were stimulated to polarize into the pro-inflammatory M1 type, secreting large amounts of pro-inflammatory cytokines (TNF-α, IL-6). However, at the LBL-GA@Mn interface, under the dual action of Mn3O4-BSA nanozyme and CS-GA, the secretion level of pro-inflammatory factors by macrophages decreased significantly, while the secretion level of anti-inflammatory cytokines (IL-10 and TGF-β) increased significantly, indicating that the bioactive interface has good anti-inflammatory properties.
[0050] Example 3 A functional titanium implant (1.5 mm in diameter and 10 mm in length) was prepared using the bioactive interface construction strategy described in Example 1. Simultaneously, a type 2 diabetes mellitus (T2DM) model was established in SD rats using a high-fat diet combined with a single intraperitoneal injection of STZ. Under aseptic conditions, the distal femur of the T2DM rats was surgically exposed, and a 1.5 mm diameter and 10 mm deep hole was drilled in the femoral condyle using a bone drill. The implant was then inserted into the bone defect site to verify the functional implant's ability to resist oxidative stress, regulate inflammation, and accelerate bone integration.
[0051] Specific experiments included: 2 days post-operation, evaluating the level of implant-peri-osseous oxidative stress marker protein (8-OHdG) using immunofluorescence staining; 7 days post-operation, evaluating the polarization level of implant-peri-osseous macrophages (all: F4 / 80, M1: CD86 / iNOS, M2 type: CD206 / Arg-1) using immunofluorescence staining; and 28 days post-operation, analyzing the volume of new bone formation and trabecular thickness around the implant using a micro-CT system, and performing morphometric statistics.
[0052] In this embodiment: Immunofluorescence staining images of 8-OHdG expression in the bone tissue surrounding different implants were tested, such as... Figure 12 As shown, the results indicate that the implants in the Ti and LBL groups exhibit strong red fluorescence, suggesting extremely high levels of the surrounding oxidative stress product 8-OHdG and severe oxidative damage to the bone tissue. In contrast, the red fluorescence intensity around the implants in the LBL-GA@Mn group was significantly reduced, indicating that the bioactive interface can alleviate tissue damage caused by oxidative stress to some extent.
[0053] Immunofluorescence staining images of M1 and M2 macrophages surrounding different titanium-based implants were tested, such as... Figure 13As shown, the results indicate that a large number of M1 macrophages infiltrate around the Ti implant, while almost no M2 macrophages are observed. This suggests that in the diabetic pathological microenvironment, the accumulation of ROS caused by hyperglycemia and excessive inflammation cause macrophages at the bone defect site to remain in a pro-inflammatory M1 phenotype, affecting the bone repair process. In contrast, almost no M1 macrophages are present around the LBL-GA@Mn implant, and a large number of M2 macrophages are present, indicating that it can effectively inhibit the polarization of macrophages to the M1 phenotype and promote the transformation of macrophages to the M2 phenotype in the diabetic pathological microenvironment.
[0054] Micro-CT images and quantitative analysis of different implants were tested, such as Figure 14 As shown, the results indicate that the LBL-GA@Mn implant exhibits good osteogenic capacity, with its surface covered by a large amount of newly formed cortical bone. Quantitative analysis showed that the bone volume volume (BV) / total volume (TV) of the newly formed bone tissue around the LBL-GA@Mn implant was significantly higher than that of other groups, indicating that bone synthesis metabolism exceeded catabolism, resulting in increased bone mass. A higher bone volume volume (BS / BV) value may indicate a rougher bone surface and poorer bone quality. The BS / BV of the bone tissue around the LBL-GA@Mn implant was significantly lower than that of other groups, indicating better bone quality. Trabecular bone number (Tb.N) and trabecular bone spacing (Tb.Sp) are the main parameters used to evaluate trabecular bone morphology. Generally, a larger Tb.N indicates more newly formed bone, while Tb.Sp refers to the distance between trabeculae; generally, greater separation indicates osteoporosis. The Tb.N of the bone tissue around the LBL-GA@Mn implant was significantly higher than that of other groups, while Tb.Sp showed the opposite trend, indicating that the LBL-GA@Mn implant can significantly promote new bone formation at the defect site.
[0055] In summary, the preparation method of this invention does not require special equipment, is simple to operate, and is highly controllable. It successfully constructs a titanium-based implant interface that can be used for the treatment of diabetic bone trauma, effectively solving the problem of the complex and variable microenvironment of diabetic bone trauma. This effectively alleviates oxidative stress, exerts immunomodulatory effects, reduces inflammatory responses, and promotes bone integration, providing a new strategy for the treatment of diabetic bone trauma. To a certain extent, it solves the current clinical problems of poor bone integration and unsatisfactory treatment efficacy of titanium implants for pathological diseases.
Claims
1. A method for preparing a surface-modified bone fracture repair implant, characterized in that Includes the following steps: Step 1: Prepare Mn3O4-BSA antioxidant nanozymes by hydrothermal method and ultrasonic treatment; Step 2: Prepare chitosan-18β-glycyrrhetinic acid conjugate CS-GA by grafting 18β-glycyrrhetinic acid onto chitosan via EDC / NHS acylation reaction; Step 3: Using layer-by-layer self-assembly technology (LBL), a gelatin / CS-GA polyelectrolyte multilayer membrane structure was constructed on the implant surface, and Mn3O4-BSA was used as the intercalation component of the multilayer membrane to prepare a bioactive surface LBL-GA@Mn modified implant.
2. The method of claim 1, wherein the surface-modified bone fracture repair implant is prepared by the steps of: a) providing a bone fracture repair implant; b) applying a surface modification to the bone fracture repair implant; and c) applying a coating to the surface modification. Step one includes: dissolving manganese acetate in ethanol, sealing the solution and heating it to react, cooling it after the reaction is complete, and centrifuging to separate the nanoparticles; adding Mn3O4 solution to BSA solution, sonicating the reaction, centrifuging to collect the nanoparticles after the reaction is complete, and the resulting product is Mn3O4-BSA nanoparticles.
3. The method of producing a surface-modified bone fracture repair implant according to claim 1 or 2, characterized in that Step two includes: preparing chitosan solution and 18β-glycyrrhetinic acid (GA) solution separately for later use; adding EDC and NHS to the GA solution to activate GA; adding the activated GA solution to the chitosan solution for reaction; and obtaining chitosan-18β-glycyrrhetinic acid conjugate CS-GA after post-treatment.
4. The method for preparing a surface-modified bone injury repair implant according to claim 1 or 2, characterized in that, Step three includes: first, preparing CS-GA solution, Gel solution, PEI solution and BSA-Mn3O4 solution for later use; then, immersing the clean implant to be modified in polyethyleneimine (PEI) solution to obtain a PEI-functionalized interface; next, immersing the PEI-pretreated implant in Gel solution, CS-GA solution and Mn3O4-BSA antioxidant nanozyme solution in sequence; repeating the immersion steps of Gel solution, CS-GA solution and Mn3O4-BSA antioxidant nanozyme solution to finally obtain an implant with an LBL-GA@Mn bioactive interface.
5. The method for preparing a surface-modified bone injury repair implant according to claim 4, characterized in that, In step three, polyethyleneimine (PEI) is used as the initiating layer, CS-GA as the cationic polyelectrolyte, gelatin (Gel) as the anionic polyelectrolyte, and Mn3O4-BSA antioxidant nanozyme as the intercalation component.
6. A surface-modified bone injury repair implant, characterized in that, It is prepared by the preparation method described in any one of claims 1-5.
7. The surface-modified bone injury repair implant according to claim 6, characterized in that, The implant is a metallic implant material including titanium, titanium alloy, stainless steel or cobalt-based alloy.